Detection of genetic diversity of SARS-CoV-2 in wastewater to monitor COVID-19 transmission - Sarwar, Subyeta Binte (Brac University, 2024)
This thesis submitted to the Department of Mathematics and Natural Sciences in partial fulfillment of the requirements for the degree of Master of Science in Biotechnology, 2023.